Moral Value In Archipelago Islamic Perspective In Children’s Stories In Bobo Magazine and Kompas Daily - Heru Kurniawan; Herman J. Waluyo; Sarwiji Suwandi; Budhi Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
After conducting research with an in-depth study of the moral aspects with the perspective of Islamic Archipelago in the children’s story on Bobo Magazine and Kompas Daily, two substantial findings were found. First, the dominant moral values in children’s stories are the value of hard work, honesty, obedience, responsibility, friendship, courage, discipline, compassion, sharing, and creativity, all of which are related to children’s moral formation. Second, values moral stories of children in the context of the Islamic archipelago related to the relationship of children’s moral values in children’s stories in the context of Islam based on the Al-Qur’an and Al-Hadits and the context of children’s moral values in children in the context of Indonesian humanity and Archipelago culture.